Educators’ Strategies in Improving the Quality of Learning for Package C Learners at PKBM Hang Tuah Pekanbaru - Hesni H; Melisha Audi Putri; Vivi Paramitha; Rika Fitri Ramadani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Community Learning Activity Centers (PKBM) are non-formal education institutions that play an important role in improving the quality of human resources through flexible learning services. The success of the learning process in PKBM is strongly influenced by the strategies used by educators in managing learning activities that are appropriate to the characteristics of the learners. This study aims to examine the strategies of educators in improving the quality of learning for Package C learners at PKBM Hang Tuah Pekanbaru. This study uses a qualitative approach with a descriptive method. The data were obtained through indirect observation of the learning process and supported by a literature review from relevant sources. Data collection techniques were carried out through documentation study and observation of learning conditions. The data were analyzed using descriptive qualitative analysis. The results show that educators’ strategies in creating a comfortable learning environment, applying flexible learning methods, and relating learning materials to daily life can improve learners’ activeness and participation in the learning process. However, there are still several challenges, such as limited learning time, differences in learners’ backgrounds, and limited learning facilities and infrastructure. Therefore, appropriate educator strategies and support from various parties are needed to improve the quality of learning in PKBM so that it can run more effectively.